Interconnections of Policies Across Territorial Borders: International Student Mobility Into Canada During the COVID-19 Pandemic - Matsumoto, Renata (Comparative and International Education / Éducation comparée et internationale, 2026)
In this paper, I examine the conditions that give rise to what is said in interviews with international students regarding a web of interconnected policies that regulated their mobility into Canada during the COVID-19 pandemic. I adopt Bacchi and Bonham’s (2016) post-structural interview analysis and focus on the production of two subject positions across the interviews: one that becomes associated with risk and one that becomes associated with resistance to certain policy processes. The participants in this study include master’s and PhD students from Brazil, China, Colombia, and India. My analysis suggests the need for an understanding of international student mobility in a more relational way that highlights the geopolitical aspects in the access to higher education in Canada for international students.